Risco de informação, custo de capital próprio e a incerteza do ambiente informacional - Oliveira, Kallyse Priscila Soares de (2019)
The disclosure of accounting information and the equity capital cost of companies are both of fundamental interest to different agents, like academics, regulators and other market participants. In this regard, many issues are raised about possible links among the factors of informational risks, which are related to the quality and distribution of information in respect to the equity capital cost of the organizations. For that reason it is necessary a distinction among the informational environments due their uncertainty. Considering this gap in the available literature, this thesis intends to take into account that the informational environment can influence the relationship between asymmetric information, quality of information and cost of equity capital. Thus, the aim of this work is to analyse the relation between the informational risk – which is represented by the quality of accounting information and the informational asymmetry – and the equity capital cost of public held companies in face of the uncertainty of the informational environment. Twelve BRICS and G7 participants – according to the International Monetary Fund (IMF) ranking – were analysed from 2010 to 2015, which give an average of 4417 companies and results in 26500 observations. The countries were grouped according to the informational environment of the economic block (emerging and developed) and credit risk (higher and lower). The model of the implied capital cost of Botosan and Plumlee (2013) was used to measure the cost of equity capital; for measurement of the discretionary accruals as a proxy for the quality of accounting information, it was used Dechow et al (2012); for informational asymmetry analysis it was used the analyst coverage, according to Clarke and Shastri (2000). With regard to the confrontation between developed and emerging markets, the results of main analysis shows that the reduction of information asymmetry influences the cost of equity capital, independently of the information environment. On the other hand, the quality of accounting information in isolation is not related to the cost of equity capital so that it starts to influence– when analyzed together with an asymmetry of information by means of interaction of variables – only in countries with developed market. Regarding the credit risk environment, the analysis of the accounting information quality variable shows that the discretionary accruals presented positive relationship in the countries with higher credit risk, and negative in the countries with lower credit risk. That make the results of the relation among between the variables conditioned to the informational environment. Concerning the information asymmetry, the results suggest that the information asymmetry by means of analysts coverage has relation to the increase of the cost of equity capital independent of the informational environment for credit risk. For the variable of interaction between information quality and informational asymmetry, the results showed that the jointly occurrence of lower quality of accounting information and a greater asymmetry of information increase the cost of equity capital and this relation is conditioned to informational environment of credit risk .